Relationship Between Knowledge and Attitudes about HIV / AIDS with Prevention Actions in Adolescents in The Jandi Village, Juhar District, Karo Regency in 2019 - Harry Dito (Institute of Computer Science (IOCS), 2020)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system, while Acquired Immunodeficiency Syndrome (AIDS) is an immune syndrome caused by HIV infection. The spread of HIV into the body turns out not only from having sex but can also be spread through needles that are used simultaneously by drug addicts, tattoo needles and can also be spread from blood transfusions, because HIV is transmitted through blood, sperm, and vaginal fluids. . This study aims to determine the relationship between knowledge and attitudes about HIV / AIDS and preventive measures in adolescents in Jandi Village, Juhar District, Karo District in 2019. As for the independent variables, namely the knowledge and attitudes of adolescents about HIV / AIDS and the dependent variable is preventive action in teenager. This type of research used analytic observational with cross sectional approach method. Where the population is teenagers as many as 30 people and the sample is 30 people. The data used are primary data taken directly from respondents using a checklist sheet, and secondary data obtained from the Village Head of Jandi. The statistical test used was the Chi-Square test α = 0.05. The results of the analysis showed that out of 30 adolescents, the majority were 12 people (40%) had less knowledge and 7 people had good knowledge of the minority (23%). Youth attitudes about HIV / AIDS were positive as many as 20 people (66%) and 10 people (34%) had a negative attitude. The majority of adolescent preventive measures against HIV / AIDS took appropriate actions as 20 (66%) and 10 (34%) did not take preventive measures.